2011
DOI: 10.1016/j.jim.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

A new model for the estimation of cell proliferation dynamics using CFSE data

Abstract: CFSE analysis of a proliferating cell population is a popular tool for the study of cell division and division-linked changes in cell behavior. Recently [13, 43, 45], a partial differential equation (PDE) model to describe lymphocyte dynamics in a CFSE proliferation assay was proposed. We present a significant revision of this model which improves the physiological understanding of several parameters. Namely, the parameter γ used previously as a heuristic explanation for the dilution of CFSE dye by cell divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
100
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(106 citation statements)
references
References 59 publications
(151 reference statements)
5
100
0
1
Order By: Relevance
“…Thus, there seems to be an advantage in the direct mathematical modeling of CFSE histogram data. To this end, structured population models have been proposed [21,22,55,56,79]. Such partial differential equation (PDE) models have long been discussed in the context of cell populations [28] and can be structured by age [1,27,39,44], cyclin content [27], size [40,44,45,68] or DNA-content [26], or any number of other physiological variables [62].…”
Section: Label-structured Pde Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, there seems to be an advantage in the direct mathematical modeling of CFSE histogram data. To this end, structured population models have been proposed [21,22,55,56,79]. Such partial differential equation (PDE) models have long been discussed in the context of cell populations [28] and can be structured by age [1,27,39,44], cyclin content [27], size [40,44,45,68] or DNA-content [26], or any number of other physiological variables [62].…”
Section: Label-structured Pde Modelsmentioning
confidence: 99%
“…The use of such a nonphysiological structure variable was suggested as early as 2000 for BrdU-based assays [30], and was first explored in the context of CFSE-based assays in [56]. More recent work [8,21,22,55,79] has consistently demonstrated that the label-structured PDE framework can accurately model the observed histogram data from a CFSE-based proliferation assay. The primary benefit of using such a model is the ability to treat CFSE histogram data directly.…”
Section: Label-structured Pde Modelsmentioning
confidence: 99%
See 3 more Smart Citations